Priming syntactic ambiguity resolution in children and adults. Issue 10 (1st December 2020) - Havron, Naomi; Scaff, Camila; Carbajal, Maria Julia; Linzen, Tal; Barrault, Axel; Christophe, Anne
ABSTRACT: Adults use their recent experience to disambiguate ambiguous sentences: Structures that have recently been primed are favoured in the resolution of different types of ambiguity, an example of structural priming. Research on children's use of recent information for disambiguation is scarce. Using a forced-choice task with a tablet, we asked whether 5–6-year-old French-speaking children could also be primed in the resolution of attachment ambiguities, as well as whether listeners are affected by the proportion of primes of each structure, and whether priming is cumulative. We found that both children and adults can be primed, and are sensitive to the proportion of structures in the input, and that priming effects cumulate as the experiment progresses. This is the first study showing priming of ambiguous sentences at 5–6 years, suggesting that children, like adults, use recent experience as a source of disambiguating information.